TEACHING SPEAKING THROUGH PROJECT-BASED LEARNING WITH ICT - Lilis Suryani; Ningtyas Orilina Argawati (University of Kuningan, 2023)
Information and communication technology (ICT) has developed recently, becoming a part of the teaching and learning process. Many studies reveal that ICT can help students learn well, including speaking. This research involved ICT and project-based learning in teaching speaking. Thus, this study aims to know the implementation of project-based learning with ICT in teaching speaking as well as the students' reactions to project-based learning with ICT in learning speaking. There were 30 participants in this study, which used classroom action research. Students from a university in Bandung who are in their second semester participate. Each cycle consists of four steps of action, observation, and reflection. Data were gathered through observation, a speaking test, and an interview. The study's conclusions showed that using ICT to execute project-based learning could improve students' speaking skills through project involvement. The results of the students greatly increased between the first and second cycles. The students gave great feedback, particularly after finishing the project. They could work in groups, became more active, learned new things, and were very motivated. They were able to actively discuss their project as well as help one another finish it. PBL can consequently boost students' enthusiasm to speak up and offer support. Keywords: classroom action research; Information and Communication Technology; project-based learning; speaking.